Bacteria isolation from skin, gills and water of Oreochromis sp. (Red Tilapia) when treated with Eisenia foetida (Oligochaete), Pleurotus sajor-caju (Oyster Mushroom), and Nepenthes gracilis (Pitcher Plant) - Nur Syuhada Rosli; Elvie John Baptist; Nor Omaima Harun (Penerbit Universiti Kebangsaan Malaysia, 2019)
Aquaculture farmers are focused on large intensive farming to fulfill the demand of protein source, thus increasing the probability of bacteria-related disease outbreak. Therefore, an alternative fish diet has to be introduced to reduce bacteriarelated infection while increasing the production. The aim of this study was to determine the microbial community on Oreochromis sp. when treated with modified diets; commercial pellet added with oligochaete (Eisenia foetida), oyster mushroom (Pleurotus sajor-caju), pitcher plant (Nepenthes gracilis) and combination of all ingredients with proportion of (90:10) and (70:10:10:10). One hundred ninety bacterial colonies from 11 species were identified using biochemical tests: Gram stain, Oxidase test, Catalase test, KOH String test, Carbohydrate (Glucose, Lactose and Sucrose) test, Indole test, Methyl Red Test and Voges-Proskauer Test (MRVP test), Citrate test and bacteria growth tested on Mannitol salt agar. Oreochromis sp. also secretes mucus that consists of protein to protect fish from pathogens with various environment conditions. Therefore, this study can be used to increase a better understanding of modified organic diet with higher protein content of microbial community in lower vertebrates.